User preference modeling for customised dynamic electronic catalogs generation based on web shoppers’ brain hemisphericity/cognitive style - A.B.M Abdullah (Penerbit UKM, 2005)
This study examined the impact of online shoppers’ brain hemisphericity/ (cognitive style) on their preference for different aspects of information presentation via electronic catalogs. Two instruments were used to measure participants’ cognitive styles/brain orientations. Pearson’s correlation ndicates that verbal and visual scores obtained by using two different questionnaires are congruent. One e-commerce survey instrument was used to measure user preferences for different features of electronic catalogs. One-way ANOVA analysis has been conducted to find out whether different VARK (visual, auditory, read/write, and kinesthetic) score groups differ significantly based on their preference for different aspects of information presentation via electronic catalogs. ANOVA results indicate that Web shoppers’ preference for text-oriented catalogs, visually-oriented catalogs, audio enabled catalogs, customisable animated catalogs, virtual trial, and online shopping differs significantly. In addition to ANOVA, regression analysis has also been conducted to reaffirm the findings of the ANOVA analysis. As expected, most of the findings in regression analysis are inline with the ANOVA results.